KERAGAMAN BUDAYA TIONGHOA PADA INTERIOR GEREJA KATOLIK - Thamrin, Diana; Arifianto, Felik (Institute of Research and Community Outreach - Petra Christian University, 2011)
The Santa Maria De Fatima Catholic Church building in West Jakarta was originally the residence of a Chinese noble around the 1900s. Although this building is used as a Catholic Church today, Chinese cultural elements are still maintained physically on the building as well as in the customs of the people of the church. The presence of various Chinese cultures in a Catholic Church makes this building an interesting object for study. This research aims to analyze and describe all the various Chinese cultures still maintained in the interior of the Catholic Church of Santa Maria De Fatima. The research method used is qualitative which is descriptive in character. The results show that various Chinese cultures are still present in the structure and layout of the building; structural elements such as beams, columns, floors, walls and ceiling; transitional elements such as doors, windows and openings; furniture as well as in the decorative elements that are similar to traditional homes and buildings in China.